Comparison of two stream gauging systems for measuring runoff and sediment yield for a semi‐arid watershed. Issue 4 (16th July 2012) - Polyakov, V. O.; Nearing, M. A.; Hawdon, A. A.; Wilkinson, S. N.; Nichols, M. H.
ABSTRACT: Our ability to understand erosion processes in semi‐arid ecosystems depends on establishing relationships between rainfall and runoff. This requires collection of extensive and accurate hydrologic and sediment data sets. A supercritical flume with a total load traversing slot sediment sampler used on several sites at the Walnut Gulch Experimental Watershed (WGEW) near Tombstone, AZ has proven to be a reliable way to measure flow and sediment discharge from small watersheds. However, it requires installation of a costly structure that is only suitable for relatively small flows. A more commonly used method based on ease of installation and expense is the pump sampler. One example of this is a set of instrumentation developed by the Australian Commonwealth Scientific and Industrial Research Organization (CSIRO), in which the pump sediment sampler is part of an in‐channel, fully automated system for measuring water velocity, depth, turbidity and collecting runoff samples. A 3.7 ha arid watershed at WGEW was instrumented with both systems and hydrologic and sediment data were collected and compared during a 2 year period. Total sediment yield for the entire period measured by the CSIRO pump sampler (11.6 t ha ‐1 ) was similar to that by traversing slot sampler (11.5 t ha ‐1 ). The pump sampler accurately estimated the amount of fine (< 0.5 mm) sediment fractions exported, but consistently underestimated the coarse (>0.5 mm) sediment fractions. Median sediment diameter of samples collected by traversing slot and pump sampler were 0.32 and 0.22 mm, respectively. This study outlines the benefits and limitations of the pump sampler based system for monitoring sediment concentration and yield in high‐energy headwater catchments, and makes recommendations for improvement of its performance. Copyright © 2012 John Wiley & Sons, Ltd.